Dystroglycan function is a novel determinant of tumor growth and behavior in prostate cancer1. Issue 4 (19th September 2012) - Mitchell, A.; Mathew, G.; Jiang, T.; Hamdy, F.C.; Cross, S.S.; Eaton, C.; Winder, S.J.
Abstract BACKGROUND Dystroglycan is a ubiquitously expressed cell adhesion molecule frequently found to be altered or reduced in adenocarcinomas, however the mechanisms or consequences of dystroglycan loss have not been studied extensively. METHODS We examined the consequence of overexpression or RNAi depletion of dystroglycan on properties of in vitro growth migration and invasion of LNCaP, PC3, and DU145 prostate cancer cell lines. RESULTS Using LNCaP cells we observed cell density‐dependent changes in β‐dystroglycan with the appearance of several lower molecular weight species ranging in size from 43 to 26 kDa. The bands of 31 and 26 kDa were attributed to proteolysis, whereas bands between 43 and 38 kDa were a consequence of mis‐glycosylation. The localization of β‐dystroglycan in LNCaP colonies in culture also varied, cells with a mesenchymal appearance at the periphery of the colony had more pronounced membrane localization of dystroglycan. Whereas some cells demonstrated nuclear dystroglycan. Increased dystroglycan levels were inhibitory to growth in soft agar but promoted Matrigel invasion, whereas reduced dystroglycan levels promoted growth in soft agar but inhibited invasion. Similar results were also obtained for PC3 and DU145 cells. CONCLUSIONS This study suggests that changes in β‐dystroglycan distribution within the cell and/or the loss of dystroglycan during tumorigenesis, through a combination of proteolysis and altered glycosylation, leads to an increased ability to grow in an anchorage independent manner, however dystroglycan may need to be re‐expressed for cell invasion and metastasis to occur. Prostate 73: 398–408, 2013. © 2012 Wiley Periodicals, Inc.